TEACHING MIXED-ABILITY CLASSES - Usmonaliyeva , Moxichexra Ma’rufjon qizi; Kosimova , Mukammal Umaraliyevna (Educational Research in Universal Sciences, 2024)
The purpose of this paper is to explore teaching mixed-ability students in educational establishments.